Flood Management in India - Mohapatra, P.K.; Singh, R.D. (2003)
In this paper, flood problems in India, regional variability of the problem, present status of the ongoing management measures, their effectiveness and future needs in flood management are covered. Flood problems in India are presented by four zones of flooding, viz. (a) Brahmaputra River Basin, (b) Ganga River Basin, (c) North-West Rivers Basin, and (d) Central India and Deccan Rivers Basin. Some special problems, related to floods like dam break flow, and water logging in Tal areas, are also mentioned. Progress of various flood management measures, both structural and non-structural, are discussed. In addition, future needs to achieve efficient and successful flood management measures in India are also pointed out. - Reproduced.
Keywords: Flood control - India; Flood control